Various Impact Resistance Capabilities of Tapioca Starch Based Shear Thickening Fluid (STF) - Saifful Kamaluddin, Muzakir; Izan Izwan, Misnon; Nazikussabah, Zaharudin (Universiti Malaysia Pahang, 2011)
STF is a non-Newtonian flow behaviour often observed in concentrated colloidal dispersions characterized by significant, sometimes discontinuous increase in viscosity with increasing shear stress. Examples are concentrated particle colloidal suspensions such as photographic dies, paints, coatings and lubricants. When such fluid is subjected to a high-enough shear stress, it can lead to a rapid, sometimes discontinuous, increase in viscosity. The change in viscosity is due to the change of molecular arrangement structure in the colloidal suspension which usually will change from disordered liquid to ordered liquid crystals. Triangle Ternary Phase Diagram can be classified as a diagram that represents the equilibrium between the various liquid crystal (LC) phases that are formed between three components.